Mulher Bruxa? Uma análise discursiva foucaultiana da desobediência de Clarice Lispector - Elias, Thaise Maria Armelin (2023)
Constantly, throughout history, women who dared to escape the confinement, once given to the feminine, were subjectified/objectified as disobedient and even as witches. They were so designated because they attacked patriarchal power, since they demonstrated skills and knowledge other than those traditionally intended for women until then. Among the innumerable and important women witches woven into history's carpet, we are interested in the emergence of the woman writer Clarice Lispector, since her life and work went against the grain of sexist discourses and reached places, until then, denied to the female subject of her time. , which earned him, among many other designations, the subject position witch. Linked theoretically and methodologically to Foucaultian Discursive Studies, we will analyze, in this research, the relationship between language, history and subject taking into account the games of truth and the discursive knots that update the utterance witch woman with reference to Clarice Lispector, one of the greatest and most important modernist writers of the 20th century. In this direction, we will articulate the archaeogenealogical formulations of Michel Foucault, specifically, statement, subject, power, objectivity and subjectivity and discursive memory, pointed out by Jean Jacques Courtine, to the history of women by Michelle Perrot and to the statute of disobedience, according to Frédéric Gros, choosing as analysis material the book Clarice, a biography of Benjamin Moser. Therefore, we will emphasize the construction of the subject through speech, that is, in Moser's discursive production about Clarice, since he takes her as the object and theme of his speech . The questions that drive this work contribute to the understanding of the socio-historical conditions of emergence of the witch utterance in the process of objectification and subjectivation of the female writer subject, Clarice Lispector, which will lead us to give visibility to the Foucauldian premise that an utterance always updates other statements.